(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The following hydronymic bases are encountered in the Mycenaean Greek dialect known from the inscriptions on slabs and vases written in the Linear B script: 4 water, river’, *H2epo-4water, flow’. *H2ekwo-4water’ and *wed- 4wet place, water’ as the heritage of a general Indo-European language. The proposed etymology for the Greek hydronym’ "Ασωπός, that it derives from the Indo-European root *H2epo-4 water, flow’, and based on the Mycenaean evidence from Knossos (KN) where it appears with a voiced labio-velar -qi- (=-#"/-): a-so-qi-jo / Asöq"ios /: Gr. "Ασώπιος (male personal name meaning „from the region of the Black River44) from the toponym "Ασωπός, must be revised and linked with the Indo-European root *H2eto- ‘water, river’ from < Indo-European. *iïsyo-*H2ek"o-, meaning *myo-H2efc’o- ‘Black River’. The author argues that the Mycenaean form m-du-ru-ta/ Widurutas/: Gr. *"Ιδυρύτας "Ιδυρίτης, is derived by means of a secondary dissimilation of the vocals -υ- υ- in -υ-1- from the Indo-European root *wedu- ‘water, life’, (cf Widuro / WiSuros / ’Ζδυρος).